Um olhar sobre o Museu Indígena Jenipapo-Kanindé: território, etnicidade e patrimônio - Freitas, Thaynara Martins (2015)
Over the last decades, a new element has arisen or been adopted by various ethnic or minority groups in Brazil, the community management museum. The museum would have been "discovered by the Indians" (FREIRE, 2003) as a potential tool for the reconstruction of memory, contributing to the process of reelaboration and strengthening of ethnic identity, political and educational mobilization. The proposal of the present anthropological research has as its field the indigenous museological experience lived by the Jenipapo-Kanindé, indigenous group located in the municipality of Aquiraz, Metropolitan Region of Fortaleza. Thus, the Jenipapo-Kanindé Indigenous Museum is a museological experience idealized and managed by the members of the community, with the support of expert and indigenist partners. Initially, it is assumed that this element is adopted by the group as a mechanism of defense and reinforcement of the affirmation of the ethnicity of this indigenous group. In search of a better understanding of this recent sociocultural and political phenomenon in the indigenous scenario of Ceará, we will make use of anthropological theoretical bases and brief museological approaches that will help to reflect on the theme proposed in this research. For this, concepts such as group and ethnic identity, memory, historical museums and ecomuseums will be essential for the accomplishment of the objective of this work. Regarding the methodology adopted, this consists of participant observation, referring to participation in events organized by this indigenous group and the other events that these were invited to participate and that have relation and relevance to the theme. In addition to a series of visits to the community with the purpose of observing the daily life of this group with the museum, with the purpose of obtaining information through conversations, semi-structured interviews and observations. Research was also conducted through videos, audios, photographs and news articles.